Bone Density, Geometry, and Mass by Peripheral Quantitative Computed Tomography and Bone Turnover Markers in Children with Diabetes Mellitus Type 1 - Maciej Jaworski; Elżbieta Wierzbicka; Edyta Czekuć-Kryśkiewicz; Paweł Płudowski; Maria Kobylińska; Mieczysaw Szalecki (Journal of Diabetes Research)
Background. The type 1 diabetes mellitus (T1DM) is a chronic systemic autoimmune-mediated disease characterised by the insulin deficiency and hyperglycaemia. Its deleterious effect on bones concerns not only bone mass, density, and fracture risk but also may involve the linear growth of long bones. Studies on the lower leg in children with T1DM by pQCT have generated conflicting results, and most of the studies published so far focused only on a selected features of the bone. An additional information about growth, modelling, and remodelling processes can be gathered by the bone turnover marker measurement. The objective of the study was to evaluate bone mineral density, mass, and geometry using peripheral quantitative computed tomography as well as bone turnover markers in the patients with type 1 diabetes mellitus. Material and Methods. Bone mineral density, mass, and geometry on the lower leg using peripheral quantitative computed tomography and serum osteocalcin (OC) and carboxyterminal cross-linked telopeptide of type 1 collagen (CTx) were measured in 35 adolescents with T1DM (15 girls) aged 12.3-17.9 yrs. The results were compared to age- and sex-adjusted reference values for healthy controls. Results. Both sexes reveal lower than zero Z-scores for lower leg 66% total cortical bone cross-sectional area to muscle cross-sectional area ratio (−0.97±1.02, p=0.002517 and −0.98±1.40, p=0.007050, respectively) while tibia 4% trabecular bone density Z-score was lowered in boys (−0.67±1.20, p=0.02259). In boys in Tanner stage 5 bone mass and dimensions were diminished in comparison to Tanner stages 3 and 4, while in girls, such a phenomenon was not observed. Similarly, bone formation and resorption were decreased in boys but not in girls. Consistently, bone turnover markers correlated positively with bone size, dimensions, and strength in boys only. Conclusions. T1DM patients revealed a decreased ratio of cortical bone area/muscle area, reflecting disturbed adaptation of the cortical shaft to the muscle force. When analyzing bone mass and dimensions, boys in Tanner stage 5 diverged from “less-mature” individuals, which may suggest that bone development in these individuals was impaired, affecting all three: mass, size, and strength. Noted in boys, suppressed bone metabolism may result in impairment of bone strength because of inadequate repair of microdamage and accumulation of microfractures.